Safety of a feed additive consisting of sodium saccharin for suckling and weaned piglets, fattening pigs, calves for rearing and for fattening (FEFANA asbl). (13th January 2023) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Fašmon Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety of sodium saccharin as a sensory feed additive (flavouring compound) for suckling and weaned piglets, fattening pigs, calves for rearing and for fattening. In a previous assessment, the Panel on Additives and Products or substances used in Animal Feed (FEEDAP Panel) could not conclude on the safety of the additive for the environment because concentrations of the additive or its degradation product 4‐hydroxysaccharin in groundwater above 0.1 μg/L were likely to occur. In addition, regarding user safety, sodium saccharin was considered to be potentially harmful by inhalation or by contact to skin and eyes. In the current opinion, the applicant restricted the use to suckling and weaned piglets and up to a use level of 5 mg/kg complete feed. In relation to the user safety, the additive was neither a skin or eye irritant, nor a dermal sensitiser. In the absence of data, the FEEDAP Panel could not conclude on the potential of the additive to be toxic by inhalation. Regarding the safety of the additive for the environment, the new conditions of use describe a maximum use level of 5 mg sodium saccharin/kg feed. The applicant indicated that a restriction to a lower use level due to environmental safety would be accepted and submitted an environment risk assessment based on a use level of 1.13 mg sodium saccharin/kg feed. This use level cannot be considered safe. The estimated use level that would result in a concentration in groundwater below 0.1 μg/L is of 0.022 mg sodium saccharin/kg feed. The available data do not allow to conclude on the potential effect of the degradation product 4‐hydroxysaccharin in ground water.